The human longevity gene homolog INDY and interleukin‐6 interact in hepatic lipid metabolism. Issue 2 (26th June 2017) - von Loeffelholz, Christian; Lieske, Stefanie; Neuschäfer‐Rube, Frank; Willmes, Diana M.; Raschzok, Nathanael; Sauer, Igor M.; König, Jörg; Fromm, Martin F.; Horn, Paul; Chatzigeorgiou, Antonios; Pathe‐Neuschäfer‐Rube, Andrea; Jordan, Jens; et al.
Abstract : Reduced expression of the Indy ("I am Not Dead, Yet") gene in lower organisms promotes longevity in a manner akin to caloric restriction. Deletion of the mammalian homolog of Indy ( mIndy, Slc13a5 ) encoding for a plasma membrane–associated citrate transporter expressed highly in the liver, protects mice from high‐fat diet–induced and aging‐induced obesity and hepatic fat accumulation through a mechanism resembling caloric restriction. We studied a possible role of mIndy in human hepatic fat metabolism. In obese, insulin‐resistant patients with nonalcoholic fatty liver disease, hepatic mIndy expression was increased and mIndy expression was also independently associated with hepatic steatosis. In nonhuman primates, a 2‐year high‐fat, high‐sucrose diet increased hepatic mIndy expression. Liver microarray analysis showed that high mIndy expression was associated with pathways involved in hepatic lipid metabolism and immunological processes. Interleukin‐6 (IL‐6) was identified as a regulator of mIndy by binding to its cognate receptor. Studies in human primary hepatocytes confirmed that IL‐6 markedly induced mIndy transcription through the IL‐6 receptor and activation of the transcription factor signal transducer and activator of transcription 3, and a putative start site of the human mIndy promoter was determined. Activation of the IL‐6–signal transducer and activator of transcription 3 pathway stimulated mIndy expression, enhanced cytoplasmic citrate influx, and augmented hepatic lipogenesis in vivo . In contrast, deletion of mIndy completely prevented the stimulating effect of IL‐6 on citrate uptake and reduced hepatic lipogenesis. These data show that mIndy is increased in liver of obese humans and nonhuman primates with NALFD. Moreover, our data identify mIndy as a target gene of IL‐6 and determine novel functions of IL‐6 through mINDY. Conclusion : Targeting human mINDY may have therapeutic potential in obese patients with nonalcoholic fatty liver disease. German Clinical Trials Register: DRKS00005450. (Hepatology 2017;66:616–630).